Analisis Pendapatan dan Kelayakan Usaha Tempe : Studi Kasus Tempe Utama Kabupaten Bojonegoro - Yudha, Danang Ananda; Masahid Masahid; Yusdiantara Yusdiantara (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2024)
Abstract. This research focuses on knowing the income and feasibility of the R/C ratio of the main tempe business in Temayang Village, Bojonegoro Regency purposively. This research analyzes the total costs incurred in one month of the tempe business to determine income, revenue and R/C ratio. The method in this analysis uses a descriptive quantitative method which shows a number scale and the respondents taken are tempe business owners. The results of the analysis show that the total costs incurred were Rp. 2,738,000, with income of Rp. 2,662,000, and the revenue obtained was Rp. 5,400,000. In the R/C ratio, there is an R/C ratio. It can be seen that the calculation results obtained are an R/C ratio of 1.97. With the guiding provisions that every R/C ratio issued is IDR. 1.00 costs incurred will get a profit of Rp. 1.97 and if the R/C is more than 1, it can be concluded that this business can be said to be worth continuing. Keywords: Income, Eligibility, and Tempe